Outcomes of Pharmacist-Led Pharmaceutical Care Interventions Within Community Pharmacies: Narrative Review - Eldooma I; Maatoug M; Yousif M (Dove Medical Press, 2023)
Ismaeil Eldooma,1,2 Maha Maatoug,2 Mirghani Yousif2 1Department of Planning, Research, and Information; National Health Insurance Fund, Wad-Medani, Sudan; 2Department of Clinical Pharmacy and Pharmacy Practice, University of Gezira, Wad-Medani, SudanCorrespondence: Ismaeil Eldooma, National Health Insurance Fund, Department of Planning, Research, and Information, Wad-Medani, Sudan, Tel +249123162135, Email esmdooma@gmail.comAbstract: Pharmaceutical care (PhC) services interventions led by pharmacists within community pharmacies (CPs) are essential in achieving optimal medication use outcomes. PhC is a concept related to medication use goals optimization through the reduction and prevention of drug-related problems (DRPs). This review paper summarized the literature on pharmacist-led PhC interventions within CPs. PubMed and Google Scholar publications were searched, identified, and summarized. Results showed that some studies handled community pharmacists' roles, and some talked about PhC interventions. However, some studies reviewed the use of medicines, adherence, and follow-up, while other groups were on counseling, patient education, and health promotion. Pharmacists integrated some studies concerning diagnosis and disease screening into community pharmacy services. Besides these studies, there were studies on system design and installation of PhC service models. Most of the identified research results showed pharmacist-led intervention benefits for patients. These benefits include reduced DRPs, clinical, economical, humane, education and knowledge, disease prevention and immunization, identification of practice process problems, and the need for current practice redesigning. In conclusion, pharmacists can help patients achieve optimal outcomes through pharmacist-led interventions. Despite mentioned results, We recommend researching comprehensively applied PhC services provision models within CPs for more pharmacists-led interventions and role activation.Keywords: pharmaceutical care, pharmacist-led interventions, community pharmacies, narrative, outcomes